Question
upstudy study bank question image url

9) \( \sqrt{\square \sqrt{490}}=\sqrt[166]{490} \)

Ask by Kirk Gordon. in Colombia
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

La incógnita □ es igual a \( \frac{1}{490^{\frac{81}{166}}} \).

Solution

Queremos encontrar el valor de la incógnita (denotémosla por □) en la ecuación   √(□ · √490) = √[166]{490}  . Para ello seguimos estos pasos: 1. Escribimos la raíz de orden 166 como potencia:   √[166]{490} = 490^(1/166). 2. Elevamos al cuadrado ambos lados para eliminar la raíz cuadrada del lado izquierdo:   (√(□ · √490))² = (490^(1/166))²,   □ · √490 = 490^(2/166). 3. Simplificamos el exponente del lado derecho:   2/166 = 1/83,   entonces   □ · √490 = 490^(1/83). 4. Despejamos □ dividiendo ambos lados por √490. Recordando que √490 = 490^(1/2) tenemos:   □ = 490^(1/83) / 490^(1/2). 5. Aplicamos la propiedad de los exponentes (división de potencias con misma base resta los exponentes):   □ = 490^(1/83 – 1/2). 6. Para calcular el exponente, buscamos un denominador común. Como 83 y 2 tienen como común denominador 166:   1/83 = 2/166  y  1/2 = 83/166.   Así, 1/83 – 1/2 = (2 – 83)/166 = -81/166. Por lo tanto:   □ = 490^(-81/166)   o de otra forma:   □ = 1/490^(81/166). Este es el valor de la incógnita en la ecuación dada.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation, first simplify the left side. We have \( \sqrt{\square \sqrt{490}} \). We know that \( \sqrt{490} \) can be expressed as \( \sqrt{49 \cdot 10} = 7 \sqrt{10} \). Therefore, if we let \( x = \sqrt{490} \), the left side becomes \( \sqrt{a \cdot x} \), where \( x = \sqrt{490} \). Next, let's take a look at the right-hand side: \( \sqrt[166]{490} \). This is the same as \( 490^{1/166} \). To solve for \( \square \), we equate both sides: \[ \sqrt{\square \cdot \sqrt{490}} = \sqrt[166]{490} \] Now, let's square both sides to eliminate the square root: \[ \square \cdot \sqrt{490} = \left(490^{1/166}\right)^2 \] Which simplifies to: \[ \square \cdot \sqrt{490} = 490^{2/166} = 490^{1/83} \] Now, isolate \( \square \): \[ \square = \frac{490^{1/83}}{\sqrt{490}} \] Since \( \sqrt{490} = 490^{1/2} \), we have: \[ \square = 490^{1/83 - 1/2} \] To combine the exponents, convert \( 1/2 \) into a fraction with a denominator of 83: \[ \square = 490^{1/83 - 41.5/83} = 490^{-40.5/83} = 490^{-40.5/83} \] Thus, the expression actually asks for \( \square \) representing a value derived from \( 490^{-40.5/83} \). The answer will retain that form—completeness and context really matter in understanding the uses of square roots in both theoretical and practical applications!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy